Active disturbance rejection control of an islanded PV/wind/battery microgrid with power quality enhancement by SAPF - Youssef Oubail; Imad Aboudrar; Mohamed El hafydy; Elmoutawakil Alaoui My Rachid; Elmahni Lahoussine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The focus in this study is on an islanded microgrid based on hybrid renewable energy sources and storage systems. This latter is considered as an essential element for all off-grid autonomous systems to offer a reliable and stable operation. The proposed system is composed of a photovoltaic system, a wind power system based on a synchronous generator and a storage system. The proposed control strategy is intended to control, through the load side converter (LSC), the AC bus voltage in terms of amplitude and frequency under different operating conditions, and to obtain, through the bi-directional battery side converter (BSC), a better regulation between the available production and the global load demand. The proposed strategy also contributes to the power quality improvement in the AC bus by controlling the PV inverter to work as a shunt active power filter to provide the required harmonic current component to non-linear loads. A new robust control strategy for internal current and voltage control loops is proposed in this research paper, it’s the active disturbance rejection control (ADRC) and it is based on the extended state observer which allows to estimate all disturbances affecting the control, such as modeling errors and parameter variations.